Changes in pulse pressure variability during cardiac resynchronization therapy in mechanically ventilated patients - Keyl, Cornelius (BioMed Central, 2007)
INTRODUCTION: The respiratory variation in pulse pressure (PP) has been established as a dynamic variable of cardiac preload which indicates fluid responsiveness in mechanically ventilated patients. The impact of acute changes in cardiac performance on respiratory fluctuations in PP has not been evaluated until now. We used cardiac resynchronization therapy as a model to assess the acute effects of changes in left ventricular performance on respiratory PP variability without the need of pharmacological intervention. METHODS: In 19 patients undergoing the implantation of a biventricular pacing/defibrillator device under general anesthesia, dynamic blood pressure regulation was assessed during right ventricular and biventricular pacing in the frequency domain (power spectral analysis) and in the time domain (PP variation: difference between the maximal and minimal PP values, normalized by the mean value). RESULTS: PP increased slightly during biventricular pacing but without statistical significance (right ventricular pacing, 33 ± 10 mm Hg; biventricular pacing, 35 ± 11 mm Hg). Respiratory PP fluctuations increased significantly (logarithmically transformed PP variability -1.27 ± 1.74 ln mm Hg(2 )versus -0.66 ± 1.48 ln mm Hg(2); p < 0.01); the geometric mean of respiratory PP variability increased 1.8-fold during cardiac resynchronization. PP variation, assessed in the time domain and expressed as a percentage, showed comparable changes, increasing from 5.3% (3.1%; 12.3%) during right ventricular pacing to 6.9% (4.7%; 16.4%) during biventricular pacing (median [25th percentile; 75th percentile]; p < 0.01). CONCLUSION: Changes in cardiac performance have a significant impact on respiratory hemodynamic fluctuations in ventilated patients. This influence should be taken into consideration when interpreting PP variation.